الدفاع عن التفسير الديني المحافظ: قراءة في تصوير دور المرأة في كتب محمد متولي الشعراوي في ضوء التحليل النقدي للخطاب - Ainurrofiq, Faiq; Ibnu Burdah; Munirul Ikhwan (Jurnal Adabiyah, 2022)
تبحث هذه المقالة في تصوير دور المرأة في كتب محمد متولي الشعراوي خاصة فيما يتعلق بعمل المرأة في القطاع العام. واختار الباحثون منهج التحليل النقدي للخطاب للكشف عن أشكال الخطابات التمييزية ضد المرأة. إضافة إلى ذلك يسعى الباحثون الكشف عن الأيديولوجية الكامنة وراء ظهور الخطابات الدينية التمييزية في تصوير دور المرأة. وبدأوا الكشف عن الخطابات التمييزية بتحليل العناصر اللغوية في مستوى البنية الكبرى والبنية العليا والبنية الصغرى. وأخيرا، قدم الباحثون ثلاث نتائج في هذه المقالة. أولا، كان الشعراوي يفرق بصورة واضحة بين دور الرجل والمرأة. يكفي على المرأة أن تعمل في القطاعات المنزلية وأما الرجل فعليه حقوق أن يعمل في القطاعات العامة. يجوز على المرأة أن تعمل في القطاعات العامة في حالة الضرورة فقط. ثانيا، هيمنة الأيديولوجية الإسلامية المحافظة الأبوية والظروف الاجتماعية حول حياة الشعراوي تؤثر كثيرا على إدراكه الاجتماعي حيث تعينه على إنتاج الخطابات التي تميل إلى تهميش دور المرأة. في هذا السياق رفض الشعراوي دعوة المساواة بين الجنسين. ثالثا، كانت الخطابات الدينية التي تهمش دور المرأة يستخدمها الشعراوي لاستجابة انتشار الحركة النسائية في مصر. من خلال هذه الخطابات الدينية التي تقيد دور المرأة يسعى الشعراوي أن يعارض انتشار أيديولوجية نسوية بل يحفظ ويداوم أيديولوجية أبوية ضد نسائية. Abstract This paper examines the representation of women's in the Muhammad Mutawalli al-Sha'rawi’s books which discusses the role of women in the public sector, especially in the workforce. The researcher used critical discourse analysis to determine the forms of discrimination in the depiction of women's roles. In addition, the author tries to find the ideological background that influences the emergence of discriminatory discourse on the role of women. The tracking of discrimination against women in the text books begins by finding discriminatory discourses at the level of the micro structure, super structure and macro structure. Finally, the authors propose three findings. First, al-Sha'rawi distinguishes between the roles of men and women. Women play a role in the domestic sphere while men play a role in the public sphere. Women are allowed to work only in urgent circumstances. Second, the dominance of an Islamic conservative anti-feminist ideology greatly affects al-Sha'rawi's social cognition in formulating religious views related to the role of women so that the discourse that emerges tends to be discriminatory against women. In this context al-Sha'rawi rejects the discourse of equality between men and women. Third, discourses on limiting the role of women in the public sphere are al-Sha'rawi's response to the establishment of feminist ideology that is developing in Egypt. By reproducing religious discourse that limits the role of women, al-Sha'rawi and other Islamists counter ideology against the feminist movement and continue to strive to maintain an anti-feminist ideology.